Modelling of a dual circuit induced draft cooling water system for control and optimisation purposes. (January 2015) - Muller, C.J.; Craig, I.K.
Abstract : Highlights: Steady-state model development for dual circuit cooling water system. Parameter estimation/fitting using genetic algorithm. Verification of model using plant data. Derivation of dynamic state-space model from the steady-state model. Abstract: The successful operation of any petrochemical plant is dependent on the use of several utilities which may include electricity, steam, compressed air, cooling media, refrigeration media, nitrogen, condensate and fuel gas. These utilities form a significant portion of the fixed cost associated with running a plant. Utility optimisation has not received much attention until recently, driven by rising energy costs, stricter environmental policies, more competitive markets, and the threat of climate change. The generation, preparation, and transportation of utilities require energy and therefore should be optimised to reduce losses and improve operating efficiency. One example of such a utility is a cooling water system. This paper describes the modelling of a dual circuit induced draft cooling water system for control and optimisation purposes. The derived model is verified with plant data indicating promising results. The model is represented in a steady-state algebraic form as well as a dynamic state-space form. This provides a convenient basis for simulation studies and controller/optimiser design.